Effect of Monochromatic Light on Circadian Rhythm of Clock Genes in Chick Pinealocytes. (2nd August 2018) - Ma, Shuhui; Wang, Zixu; Cao, Jing; Dong, Yulan; Chen, Yaoxing
Abstract: The avian circadian system is a complex of mutually coupled pacemakers residing in pineal gland, retina and suprachiasmatic nucleus. In this study, the self‐regulation mechanism of pineal circadian rhythm was investigated by culturing chick primary pinealocytes exposed to red light (RL), green light (GL), blue light (BL), white light (WL) and constant darkness (DD), respectively. All illuminations were set up with a photoperiod of 12 light: 12 dark. The 24‐h expression profiles of seven core clock genes ( cBmal1/2, cClock, cCry1/2 and cPer2/3 ), cAanat and melatonin showed significant circadian oscillation in all groups, except for the loss of cCry1 rhythm in BL. Compared to WL, GL increased the amplitudes and mesors of positive elements ( cClock and cBmal1/2 ) and reduced those of negative elements ( cCry1/2 and cPer2/3 ), in contrast to RL. The temporal patterns of cAanat mRNA and melatonin secretion have always been consistent with the positive genes. Besides, GL advanced the acrophases of the positive elements, cAanat and melatonin, but RL and BL showed the opposite effect. Thereby, GL could promote the secretion of melatonin by enhancing the expressions of positive clock genes and repressing the expressions of negative clock genes. Abstract : The chick pinealocytes could receive external monochromatic light stimulation. Green light increased the expression of the positive clock genes ( cBmal1, cBmal2 and cClock ) and decreased the expression of the negative clock genes ( cCry1, cCry2, cPer2 and cPer3 ) to promote cAanat expression and melatonin secretion in chick pinealocytes.